(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The play conception determining the XX century culture comes from the ancient times till modern period. Even Plato, then Aristotle spoke of play’s thinking peculiarity and appreciated it as the main feature of mimesis. The play as a cultural event, as a part of the culture, was in the center of attention of representatives of German romanticists, tried to determine a scientific basis of it. At the beginning of the XX century Johan Huizinga in his work «Homo Ludens» presented the «culture as a play» conception, appreciates «a playing man» as a phenomenon. J. Huizinga’s «play conception» is shown in the postmodernist aesthetics point of view such as in the discourses of R. Barthes, J. Deleuze, Y. Kristeva, J. Baudrillard. In postmodern prose, the notions such as play with the text, play within the text, metalanguage play, and carnival trickery are based on the «culture as a play» conception. The idea of the center’s being not one but several makes the history seemed serious common, historical hero transforms into the common person, falls down into total irony by the postmodernist play principle. If there exists no certain truth, if the truth is many-sided then the idea of «the past is not the notion to be imitated» comes from here. The history not imitated, «removing» of seriousness transforms into imagination. Imagination may be a play material. The borders of serious things almost worshiped for many years by people go through their spirit and intellect, the removal of borders means seriousness becoming imagination. The transforming something into «play» element has the goal to show its notion hidden in the deepest levels. The postmodernist writers based on the thoughts that human’s thought is not objective but subjective laughs at objectivism mocks its seriousness,the fore it transforms into the play element.